Análisis del proceso administrativo de la Compañía Mundialcorp S. A. ubicado en el sector Albonor de la ciudad de Guayaquil. - Troya Lucio, Lady Susana (2022)
The objective of this work is to analyze the administrative process that occurs within the company MUNDIALCORP SA located in the city of Guayaquil, this company is focused on works in the construction area, in order to obtain accurate data for this analysis, research techniques were used. such as a direct interview with the owner of the company and observation sheets made to the collaborators, the results obtained show that within the company the corresponding administrative processes are not being carried out, that is, the organization does not have an integrated administrative process, the manager performs the activities empirically due to ignorance of what an administrative process is and how it should be applied, causing this to have repercussions on organizational performance such as the achievement of the objectives established in an ideal way.